Solar and Human Activity Impact on High and Low Land River Flows - Arban Berisha (Salehan Institute of Higher Education, 2023)
In the last two decades, in the Kosovo area, we have seen extraordinary climate changes and their consequences, such as flash floods, empty reservoirs, and forest burning. So, the objective of this article is to analyze the main drivers of climate change due to global warming, like Temperatures, Precipitation, River flows (TPQ), Human Activity (HA) on one side and the extraterritorial factor of sunspot number NS on the other side. The methodology of the approach is statistical, with trend detection, comparison, and calculation of significance for each factor. There are data in state institutions, daily and monthly, for TPQ from 1963â€“2022 and Sunspots from 1954â€“2006. Three Highland HL, two Lowland LL rivers, and two Temperature and Precipitation Meteorological stations were considered for analysis. For river LL1, the data needed to be completed, and correlation, calibration, and validation methods were applied to fill the gaps. Results indicate that sunspot numbers show a decrease of -18% from the average value, Temperature +24%, Precipitation +5%, HL1 flow -31%, HL2 -0.5%, HL3 -7.5%, LL1 -22%, and LL2 -13%. The significance of the impact of Sunspots on the air temperature approximates 75%, while the impact of human activity approximates 25%. This will be an excellent contribution to future water resource management plans.Â Doi: 10.28991/CEJ-2023-09-07-06 Full Text: PDF